Impact of mouse model tumor implantation site on acquired resistance to anti-PD-1 immune checkpoint therapy - Denis, Morgane; Mathé, Doriane; Micoud, Manon; Choffour, Pierre-Antoine; Grasselly, Chloé; Matera, Eva-Laure; Dumontet, Charles (Frontiers in Immunology, 2023)
The use of tumor subcutaneous (SC) implantations rather than orthotopic sites is likely to induce a significant bias, in particular, in the field of immunotherapy. In this study, we developed and characterized MC38 models, implanted subcutaneously and orthotopically, which were either sensitive or rendered resistant to anti-PD1 therapy. We characterized the tumor immune infiltrate by flow cytometry at baseline and after treatment. Our results demonstrate several differences between SC and orthotopic models at basal state, which tend to become similar after therapy. These results emphasize the need to take into account tumor implantation sites when performing preclinical studies with immunotherapeutic agents.